#1**0 **

Solve the following system:

{4 q + 3 p = 8 | (equation 1)

3 q + 4 p = 13 | (equation 2)

Swap equation 1 with equation 2:

{4 p + 3 q = 13 | (equation 1)

3 p + 4 q = 8 | (equation 2)

Subtract 3/4 × (equation 1) from equation 2:

{4 p + 3 q = 13 | (equation 1)

0 p+(7 q)/4 = -7/4 | (equation 2)

Multiply equation 2 by 4/7:

{4 p + 3 q = 13 | (equation 1)

0 p+q = -1 | (equation 2)

Subtract 3 × (equation 2) from equation 1:

{4 p+0 q = 16 | (equation 1)

0 p+q = -1 | (equation 2)

Divide equation 1 by 4:

{p+0 q = 4 | (equation 1)

0 p+q = -1 | (equation 2

**p = 4 and q= -1**

Guest Oct 1, 2020